The Luteinizing Hormone Receptor Knockout Mouse as a Tool to Probe the in Vivo Actions of Gonadotropic Hormones/Receptors in Females - Jonas Karol; Rivero Müller Adolfo; Oduwole Oduwole; Peltoketo Hellevi; Huhtaniemi Ilpo (Endocrine Society, 2022)
Mouse models with altered gonadotropin functions have provided invaluable insight into the functions of these hormones/receptors. Here we describe the repurposing of the infertile and hypogonadal luteinizing hormone receptor (LHR) knockout mouse model (LuRKO), to address outstanding questions in reproductive physiology. Using crossbreeding strategies and physiological and histological analyses, we first addressed the physiological relevance of forced LHR homomerization in female mice using BAC expression of 2 ligand-binding and signaling deficient mutant LHR, respectively, that have previously shown to undergo functional complementation and rescue the hypogonadal phenotype of male LuRKO mice. In female LuRKO mice, coexpression of signaling and binding deficient LHR mutants failed to rescue the hypogonadal and anovulatory phenotype. This was apparently due to the low-level expression of the 2 mutant LHR and potential lack of luteinizing hormone (LH)/LHR-dependent pleiotropic signaling that has previously been shown at high receptor densities to be essential for ovulation. Next, we utilized a mouse model overexpressing human chorionic gonadotropin (hCG) with increased circulating "LH/hCG"-like bioactivity to ~40 fold higher than WT females, to determine if high circulating hCG in the LuRKO background could reveal putative LHR-independent actions. No effects were found, thus, suggesting that LH/hCG mediate their gonadal and non-gonadal effects solely via LHR. Finally, targeted expression of a constitutively active follicle stimulating hormone receptor (FSHR) progressed antral follicles to preovulatory follicles and displayed phenotypic markers of enhanced estrogenic activity but failed to induce ovulation in LuRKO mice. This study highlights the critical importance and precise control of functional LHR and FSHR for mediating ovarian functions and of the potential repurposing of existing genetically modified mouse models in answering outstanding questions in reproductive physiology. © 2021 The Author(s). Published by Oxford University Press on behalf of the Endocrine Society.